Perancangan User Experience Situs Web Tanoto Scholars Association Brawijaya Malang menggunakan Metode Goal-Directed Design (GDD) - Stefanus Anugrah Pribadi; Retno Indah Rokhmawati; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tanoto Scholars Association at Brawijaya University, asks for a good and easy to use website design for users in getting the information needed related to the scholarship program. So far, many users have had difficulty using the primary Tanoto Foundation website because they are structuring information and displays that are not appropriate. This study aims to produce TSA UB website design using the Goal-Directed Design (GDD) method which consists of six phases. Research phase, get the needs and needs desired by stakeholders and users with the results is statement of work. Modeling phase, produces user persona with seven variables, retrospective and prospective user journey. Requirements Phase, produce scenario contexts and adjust the needs of the website with the environment. Framework phase, create a web-based interface using wireframe. The refinement phase to perfects the interface framework in the form of high-fidelity prototype. The last is Support phase, conducting qualitative and quantitative testing with user testing techniques on six respondents and with the SUPR-Q questionnaire technique on 20 respondents were analyzed based on the scale of usability scale. The results of the SUPR-Q questionnaire provide aspects of usefulness, credibility, appearance and loyalty with all aspects valued at 75.81% (category C) which is good and acceptable so that it can be used on a website that is developed as a whole and can be accepted by respondents.